Re-evaluating the Psalterium Sinaiticum: the Limitations of Internal Reconstruction as a Text-Critical Method - MacRobert, Catherine Mary (Poznańskie Studia Slawistyczne, 2018)
The Psalterium Sinaiticum, a Glagolitic manuscript containing an Old Church Slavonic version of the Book of Psalms, has usually been treated, since its discovery in the later nineteenth century, as representative of the translation made by SS Cyril and Methodius before 869. Yet its textual status is in two ways problematic: it exhibits a number of idiosyncratic features (verse divisions, headings, variant readings, lexical peculiarities) which set it apart from other Church Slavonic psalter manuscripts, even those which are generally referred to the same early redaction and Cyrillo-Methodian tradition; it displays marked internal inconsistencies for which there is no simple explanation, such as correlation with the various changes of scribal hand in the manuscript. Von Arnim used the distribution of these inconsistencies as evidence to support an internal reconstruction of several distinct stages in the manuscript tradition underlying the Psalterium Sinaiticum. His argumentation implies that in fact the text of this manuscript stands at some distance from the original translation of SS Cyril and Methodius. On the basis of new comparative evidence from the second Glagolitic psalter manuscript discovered on Sinai in 1975, this paper reviews von Arnim’s analysis and its effectiveness as a text-critical method, and draws conclusions about the place of the Psalterium Sinaiticum in the Cyrillo-Methodian tradition.